Molecular Dynamic Simulation of Crude Oil (SARA) Water Flooding Mechanisms under Different Driving Forces in Oleophilic Pore Channels - Wenguo Ma; Ruilin Ma; Peng Wang (Geofluids)
This study investigates the variation of crude oil density distribution with water flooding time for different driving force conditions in the oleophilic pore channel. We used molecular dynamic simulations to analyze the dynamic processes of transport and attachment of crude oil molecules in the pore channel under different driving forces. Oil molecule density distribution pattern during water flooding is of great significance to explore the water flooding mechanism. We studied the oil-water and oil-wall interaction energy. The oil-water interaction energy increased slightly with the increase in the driving forces. The oil-wall interaction energy grew with the increase in the driving forces between 0.001 kcal/(mol·Å) and 0.003 kcal/(mol·Å). When the driving forces increased to 0.004 kcal/(mol·Å) and 0.005 kcal/(mol·Å), the oil-wall interaction energy increased with the increase in the driving forces. After 0.003 kcal/(mol·Å), the oil-wall interaction energy decreases to different degrees. Then, we conducted the RDF analysis to compare the changes of peak value on the RDF between the crude oil and the hydrogen atoms in the wall at distinct moments of time for the three driving forces. We can see that the peak is constant between 5 Å and 6 Å as the driving forces increase. We also analyzed the number density of the crude oil and found that the difference in the number density of the crude oil molecules attached to the two sides of the wall becomes more pronounced as the driving forces are accumulated. The plot of the center-of-mass velocity at different driving forces shows the decrease in center-of-mass velocity as the driving forces increase. We also provided graphs of oil density distribution and the velocity distribution at each moment. Those graphs clearly demonstrated that the side of the wall with more crude oil attached attracts oil droplets; then, the water gradually piled the crude oil up to form oil clusters. High-speed water molecules will strip the oil molecules in the middle of the pore.